Analysis of Agricultural-Subsector Contribution through Economic Development of Nigeria 1981-2020 - Raufu, Mufutau; Fajobi, Deborah Tosin; Adesiyan, Israel; Miftaudeen-Raufu, Abdussalam; Shafa'tu , Nabage; Babatunde, Oluwakemi (PT. Riset Press International, 2025)
Stagnation in agriculture is the principal explanation for poor economic performance in many developing economies of the world, and rising agricultural productivity is the core reason for successful industrialization. The study analyzed the contribution of agricultural subsector to the economic development of Nigeria. Secondary data were sourced from various issues of Central Bank of Nigeria (CBN) annual reports and statement of account, Statistical Bulletin between 1981 – 2020. The study employed a unit root test for stationarity, cointegration test of long-run relationship to avoid spurious regression, Ordinary Least Square to investigate the impact of all the independent variables (Agricultural subsectors) on the dependent variable (GDP). The Granger causality test was used to test the causal relationship between the time series data. The null hypothesis for the unit root and cointegration were rejected. The result of the regression analysis showed a good fit with high R2, and some of the variables were significant. Some of the variables have unidirectional causality between each other, but there is no causal relationship between some of them. The study recommends that forest resources should be better harnessed to contribute more to the nation's gross domestic product. Also, the use of improved livestock breeds should be encouraged to improve their output further.